Measuring professional identity formation early in medical school. (4th March 2017) - Kalet, Adina; Buckvar-Keltz, Lynn; Harnik, Victoria; Monson, Verna; Hubbard, Steven; Crowe, Ruth; Song, Hyuksoon S.; Yingling, Sandra
Abstract: Aim: To assess the feasibility and utility of measuring baseline professional identity formation (PIF) in a theory-based professionalism curriculum for early medical students. Methods: All 132 entering students completed the professional identity essay (PIE) and the defining issues test (DIT2). Students received score reports with individualized narrative feedback and wrote a structured reflection after a large-group session in which the PIF construct was reviewed. Analysis of PIEs resulted in assignment of a full or transitional PIF stage (1–5). The DIT2 score reflects the proportion of the time students used universal ethical principles to justify a response to 6 moral dilemma cases. Students' reflections were content analyzed. Results: PIF scores were distributed across stage 2/3, stage 3, stage 3/4, and stage 4. No student scores were in stages 1, 2, 4/5, or 5. The mean DIT2 score was 53% (range 9.7?76.5%); the correlation between PIF stage and DIT score was ρ =  0.18 ( p  = 0.03). Students who took an analytic approach to the data and demonstrated both awareness that they are novices and anticipation of continued PIF tended to respond more positively to the feedback. Conclusions: These PIF scores distributed similarly to novice students in other professions. Developmental-theory based PIF and moral reasoning measures are related. Students reflected on these measures in meaningful ways suggesting utility of measuring PIF scores in medical education.